2008
DOI: 10.1016/j.taap.2007.12.030
|View full text |Cite
|
Sign up to set email alerts
|

Fullerene C60 exposure elicits an oxidative stress response in embryonic zebrafish

Abstract: Due to its unique physicochemical and optical properties, C 60 has raised interest in commercialization for a variety of products. While several reports have determined this nanomaterial to act as a powerful antioxidant, many other studies have demonstrated a strong oxidative potential through photoactivation. To directly address the oxidative potential of C 60 , the effects of light and chemical supplementation and depletion of glutathione (GSH) on C 60 -induced toxicity were evaluated. Embryonic zebrafish we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
113
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(118 citation statements)
references
References 40 publications
(70 reference statements)
3
113
1
1
Order By: Relevance
“…A concentration at 50 μM NAC has been previously been shown to be safe, and to effectively eliminate ROS in zebrafish embryos (Usenko et al, 2008;Liu et al, 2015).…”
Section: Ros Measurement Lipid Peroxidation Assessment and Antioxidmentioning
confidence: 99%
“…A concentration at 50 μM NAC has been previously been shown to be safe, and to effectively eliminate ROS in zebrafish embryos (Usenko et al, 2008;Liu et al, 2015).…”
Section: Ros Measurement Lipid Peroxidation Assessment and Antioxidmentioning
confidence: 99%
“…Several in vivo and in vitro tests have confirmed that C 60 can induce a variety of irreversible adverse effects, especially DNA damage [16,17,25,26]. Our study shows that C 60 can cleave pBR322 plasmid DNA at room temperature without photoactivation.…”
Section: Discussionmentioning
confidence: 51%
“…Protein concentration increased in the bronchoalveolar lavage fluid (BALF), but the toxicological effect was minimal. In vivo toxicological studies using fishes 19,27,32) reported significant lipid peroxidation in the brain, a decrease in the hatching rate of the zebra fish embryo, and fin malformation. Such C60 toxicity could be decreased by a dose of antioxidant, thus the damage was presumed to be caused by the generation of peroxides or free radicals.…”
Section: Fullerene (C60)mentioning
confidence: 99%